Metallic Inverse Opal Frameworks as Catalyst Supports for High‐Performance Water Electrooxidation. Issue 20 (23rd September 2022) - Nguyen, Tam D.; Hoogeveen, Dijon A.; Cherepanov, Pavel V.; Dinh, Khang N.; van Zeil, Daniel; Varga, Joseph F.; MacFarlane, Douglas R.; Simonov, Alexandr N.
Abstract: High intrinsic activity of oxygen evolution reaction (OER) catalysts is often limited by their low electrical conductivity. To address this, we introduce copper inverse opal (IO) frameworks offering a well‐developed network of interconnected pores as highly conductive high‐surface‐area supports for thin catalytic coatings, for example, the extremely active but poorly conducting nickel‐iron layered double hydroxides (NiFe LDH). Such composites exhibit significantly higher OER activity in 1 m KOH than NiFe LDH supported on a flat substrate or deposited as inverse opals. The NiFe LDH/Cu IO catalyst enables oxygen evolution rates of 100 mA cm −2 (727±4 A gcatalyst −1 ) at an overpotential of 0.305±0.003 V with a Tafel slope of 0.044±0.002 V dec −1 . This high performance is achieved with 2.2±0.4 μm catalyst layers, suggesting compatibility of the inverse‐opal‐supported catalysts with membrane electrolyzers, in contrast to similarly performing 10 3 ‐fold thicker electrodes based on foams and other substrates. Abstract : Thin but successful : An interconnected three‐dimensional network of inverse opal metallic substrates provides substantial improvements in water electrooxidation activity for the sustainable production of clean H2 . The present work showcases the use of highly conductive copper inverse‐opal support to produce micrometer‐thick anodes enabling water oxidation rates similar to those achieved with mm‐thick electrodes.